Estudo de técnicas de preparo de amostra para determinação do Ácido Fenilmercaptúrico urinário por Cromatografia Gasosa Acoplada à Espectrometria de Massas para avaliação da exposição ao benzeno. - Vanessa Gonçalves Milagres (2018)
Biological monitoring or biomonitoring involves the measurement of chemical substances, or their respective metabolites, which are quantified in biological fluids such as urine and blood. Thus, an estimation of human exposure to such substances is allowed. Benzene, which is a ubiquitous pollutant, is one of the targets of widespread toxicological concern and biological monitoring in places where occupational or environmental exposure occurs. Such interest is related to its adverse health effects, such as hematotoxic effects and carcinogenicity, which are associated with prolonged exposure to this solvent. Since benzene causes hematotoxicity at levels below 1 ppm, the identification of sensitive and specific biological markers is crucial for defining the exposure to low levels of benzene concentration and for assessing the health risk that such exposure may provide. Phenylmercaptoric acid is a benzene metabolite that has been considered a specific and sensitive biomarker since it is not present in the urine of non-exposed and has a correlation with benzene in the air at low concentrations. However, benzene presents a challenge as a biomarker because of the analytical methodology, since it is excreted in the urine in a very low proportion, thus requiring high cost techniques and complex procedures to ensure adequate analytical sensitivity. Thus, the present study aimed to develop and standardize the analytical procedure for determination of Urinary Phenylmercaptúrico Acid using Gas Chromatography Coupled to Mass Spectrometry, with subsequent validation of the methodology and application in real samples of workers of resellers of fuels, who are occupationally exposed to benzene. The method used in the study was linear in a concentration range of 5 to 60 g / L, with detection and quantification limits of 0.95 g / L and 3.18 g / L, respectively. The method presented intra and inter-assay precision with coefficients of variation of 3.63 and 8.67%, respectively, and an average accuracy of 98.72%, whose parameters were adequate and satisfactory for quantification of phenylmercuric acid in urine. Regarding the analyzes of the urine samples, it was observed that AFM values ranged from 0.61 to 14.60 g / g creatinine and that the mean was 4.58 g / g creatinine.